THE CONCEPTS OF CONSCIOUSNESS AND UNCONSCIOUSNESS IN THE INTERPRETATION OF SIGMUND FREUD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Sigmund Freud analyzed the states of consciousness and unconsciousness in human activity in his work entitled “Psyche of the Unconscious”. According to him, these states cannot be separated from each other, because some elements of the unconscious are found in the conscious state. In Europe, the conscious activity of a person was one of the first to be interested in his psyche, interpreting consciousness as a mental process.